The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1515/hfsg.1992.46.6.495
|View full text |Cite
|
Sign up to set email alerts
|

The Reactions of Hydroxyl Radicals with Aromatic Rings in Lignins, Studied with Creosol and 4-Methylveratrol

Abstract: Creosol and its methyl ether (4-methylveratrol), two simple model compounds representing phenolic and non-phenolic nuclei in lignins, were reacted in aqueous solution at ambient temperature and pressure with hydroxyl radicals generated by -radiolysis. The reactions were conducted at different pH levels (2-12) and in the presence and absence of oxygen. After fractionation of the reaction mixtures, more than 40 products from each model compound were identified by HPLC-UV, GC-MS and/or NMR analyses. In some cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 8 publications
2
49
0
Order By: Relevance
“…This analogy is reasonable since the main intermediates involved in such reactions are believed to be phenoxy radicals. 20 The phenolic diphenylmethane and a-5 structures, 8 and 13, respectively, were found to be remarkably more reactive than the 5-5 H dicreosol model compound 1, that was degraded by the laccase treatments only in low amounts. The diphenylmethane model 8, which showed the highest reactivity, also showed the highest amount of high molecular weight metabolites, probably arising from radical coupling reactions.…”
Section: Discussionmentioning
confidence: 94%
“…This analogy is reasonable since the main intermediates involved in such reactions are believed to be phenoxy radicals. 20 The phenolic diphenylmethane and a-5 structures, 8 and 13, respectively, were found to be remarkably more reactive than the 5-5 H dicreosol model compound 1, that was degraded by the laccase treatments only in low amounts. The diphenylmethane model 8, which showed the highest reactivity, also showed the highest amount of high molecular weight metabolites, probably arising from radical coupling reactions.…”
Section: Discussionmentioning
confidence: 94%
“…Intracellular hydroxylation was also observed in white rot fungi: Phanerochaete chrysosporium produced 4,5-dichlorocatechol from 3,4-dichlorophenol (5). Aromatic hydroxylation involving chemically generated hydroxyl radicals has been studied with a variety of compounds (10,21,22). From salicylic acid, congeners hydroxylated in ortho and para positions were formed: the generation of 2,3-dihydroxybenzoate and 2,5-dihydroxybenzoate has been used to detect hydroxyl radicals (7,13).…”
Section: Discussionmentioning
confidence: 99%
“…Barr and Aust (1994) and Gierer et al (1992) discussed depolymerization and repolymerization of lignin in the presence of hydroxyl radicals, and Goodell et al (1997) suggested that a similar mechanism existed in brown rot when the chelator-mediated Fenton reaction was active. More recent research suggests that brown-rot fungi have a greater ligninolytic capability (Arantes et al 2009aYelle et al 2008Yelle et al , 2011Martinez et al 2011) than previously thought (Agosin et al 1989;Eriksson et al 1990).…”
Section: Lignin Oxidationmentioning
confidence: 99%